Phishing Attack Simulation: Measuring Susceptibility among Undergraduate Students - Hanis Binti Tuan Kob T.N.; Rahim F.A.; Azman F. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer crime; High rate; Internet usage; Internet users; Malaysians; Phishing attacks; Undergraduate students; Students